Hybridilaina suomalaisilla arvopaperimarkkinoilla - Myllymäki, Janne (Helsinki Law Review, 2013)
This article discusses the legal position and use of hybrid loans in the Finnish securities market. The term ‘hybrid instruments’ refers to financial instruments, which feature qualities of both equity and debt. A hybrid loan may therefore be defined as a debt instrument, which also includes characteristics pertinent to equity instruments. !e use of hybrid loans may be beneficial in certain ways compared to the use of pure equity and debt instruments. Nevertheless, hybrid loans have primarily been introduced to the Finnish securities market during times of financial crisis. This article examines the phenomenon of hybrid loans from the perspective of the Finnish legal system. The first part of the article describes the qualities of hybrid loans from a legislative perspective, while the second part mainly focuses on the regulation of the securities market, especially with regard to the issuing of securities and reporting.